Make: electronics : learning by discovery - Platt, Charles (O'Reilly Media, 2009)
""This is teaching at its best!"" --Hans Camenzind, inventor of the 555 timer (the world's most successful integrated circuit), and author of Much Ado About Almost Nothing: Man's Encounter with the Electron (Booklocker.com) ""A fabulous book: well written, well paced, fun, and informative. I also love the sense of humor. It's very good at disarming the fear. And it's gorgeous. I'll be recommending this book highly."" --Tom Igoe, author of Physical Computing and Making Things Talk Want to learn the fundamentals of electronics in a fu.